Responses of above- and below-ground carbon stocks to environmental drivers in Tibetan Alpine grasslands - Liu, Hongsheng; Miao, Zewei (Journal of Environmental Engineering and Landscape Management, 2016)
Paucity in the knowledge of responses of grassland carbon dynamics to environmental variables constrains our ability to predict future ecosystem productivity. The aim of this study was to investigate differential responses of above- and below-ground carbon stocks to environmental drivers in Tibetan alpine Plateau at both regional and local scales. Variance partitioning and non-linear regression between carbon stocks and environmental driving variables suggested that both above- and below-ground carbon stocks showed a significant negative relationship with temperature and a positive relationship with soil moisture. Annual accumulated temperature constrained above-ground carbon at regional scale (r2 = 0.50, P < 0.0001), while soil moisture controlled below-ground carbon at local scale (r2 = 0.48, P < 0.0001). Scale-specific responses of above- and belowground carbon storage to temperature and soil moisture complicated the influences of abiotic environmental variables on ecosystem productivity. Soil carbon had significant unimodal (r2 = 0.11, P = 0.0073) and linear (r2 = 0.37, P < 0.0001) relationships with mean annual temperature and soil moisture, respectively. Since the driving factors of aboveground and soil carbon content are specific to spatial scales, the relationships of grassland carbon storage and environmental factors at small scales are not applicable to a large spatial scale.